A global meta-analysis of floral longevity reveals widespread plasticity and ecological correlates - Xu, Yue-Wen; Qian, Li-Shen; Sun, Lu; Sun, Hang; Arroyo, Mary T. K.; Song, Bo (My University, 2025)
Plasticity of floral longevity (FL) in response to pollination enables plants to maximize opportunities for pollen receipt and export under unfavorable pollination conditions, while minimizing costs under favorable ones, playing a crucial role in plant pollination. However, the prevalence of floral longevity plasticity (FLP) across the angiosperms remains unclear. Using data for FL consisting of 397 comparisons from 188 species, we provide the first global, cross-species quantification of FLP and assess its association with a range of biotic and abiotic factors. Supplementary or hand cross-pollination significantly shortened FL by 21.39%, while pollinator exclusion extended it by 34.66%, compared to natural pollination conditions. FLP was not constrained by phylogeny. Plants at higher elevations, where pollinator conditions tend to be deficient, showed longer FL under open pollination. Additionally, plasticity was found to be trait-specific, with greater plasticity observed in species with high construction and maintenance costs as well as in those that are prone to pollen limitation. Furthermore, FLP was greater under higher temperatures, more severe drought conditions, and greater climatic variability. Our findings suggest that the ability to plastically adjust FL is widespread among angiosperms, with potential implications for plant responses to global change.
Keywords: floral longevity; global change; meta-analysis; phenotypic plasticity; pollen limitation